A conserved role for sleep in supporting Spatial Learning in Drosophila - Melnattur, Krishna (Sleep, 2020)
Sleep loss and aging impair hippocampus-dependent Spatial Learning in mammalian systems. Here we use the fly Drosophila melanogaster to investigate the relationship between sleep and Spatial Learning in healthy and impaired flies. The Spatial Learning assay is modeled after the Morris Water Maze. The assay uses a “thermal maze” consisting of a 5 × 5 grid of Peltier plates maintained at 36–37°C and a visual panorama. The first trial begins when a single tile that is associated with a specific visual cue is cooled to 25°C. For subsequent trials, the cold tile is heated, the visual panorama is rotated and the flies must find the new cold tile by remembering its association with the visual cue. Significant learning was observed with two different wild-type strains—Cs and 2U, validating our design. Sleep deprivation prior to training impaired Spatial Learning. Learning was also impaired in the classic learning mutant rutabaga (rut); enhancing sleep restored learning to rut mutants. Further, we found that flies exhibited a dramatic age-dependent cognitive decline in Spatial Learning starting at 20–24 days of age. These impairments could be reversed by enhancing sleep. Finally, we find that Spatial Learning requires dopaminergic signaling and that enhancing dopaminergic signaling in aged flies restored learning. Our results are consistent with the impairments seen in rodents and humans. These results thus demonstrate a critical conserved role for sleep in supporting Spatial Learning, and suggest potential avenues for therapeutic intervention during aging.